Strategi Pemasaran Harian Bisnis Indonesia pada Perwakilan Makassar - Sabri Hasan (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
This study aims to identify internal factor and external factor companies that can become strengths, weaknesses, opportunities, threats for the company. The study was descriptive method. The collected data was processed and analyzed qualitatively and quantitatively. The data are processed and analyzed for the formulation of strategy by using the method of data processing based on SWOT analysis. The results of the study indicate that the position of the company’s strategy is at the average position in utilizing its strengths to deal with its internal weaknesses, which the company’s main strength is the presence of insertions. East regional page, while its main weakness is the limited market for Just the business world. IE Matrix analysis results show current position is at V cell, where the strategy must run the company is to maintain and preserve (hold and maintain), consisting of: market penetration strategies and product development. SWOT matrix analysis results indicate that marketing strategies that can be selected by the company to be considered are: maintaining the quality of the East Regional Inserts advertisements, expand market segmentation, add advertising agency, effective promotional activities, maintain and defend existing market area, and maintain prices relatively cheaper than competitors’ prices, and expand the larger market share through a more vigorous marketing efforts.Keywords: Internal Factors, External Factors, SWOT Analysis.